PVDF-alumina and PVDF-bentonite hollow fiber membrane for CO2 absorption via membrane contactor - Izzati, Ahmad Rudaini (2019)
PVDF hollow fiber membrane contactor system was improved by the addition of alumina and bentonite in terms of membrane structure and wetting resistance. Polyvinylidene fluoride (PVDF) polymer was modified by varying different concentration of alumina and bentonite (1 wt%, 3wt% and 5 wt%). Polymer dope solution (18 wt%) with various concentration of (alumina and bentonite) had been prepared and the hollow fiber membrane was fabricated using wet spinning process. CO2 absorption was conducted using 1 M and 2 M of Monoethanolamine (MEA) as liquid absorbent. The hollow fiber membranes were characterized by using contact angle measurement, gas permeation test and tensile strength test to investigate the mechanical properties and membrane structure. Scanning electron microscope (SEM) and atomic force microscope (AFM) were used to investigate the membrane morphology and surface roughness of the membrane. The introduction of alumina and bentonite to polymer dope solution had improved the PVDF hollow fiber membrane characteristic, including membrane hydrophobicity and CO2 absorption flux. The formation of sponge-like structure and finger-like structure in the membrane was developed by ranging different concentration of alumina and bentonite. Increasing the alumina and bentonite concentration in PVDF dope solution produced more sponge-like structure. The membrane with more sponge-like structure produced high hydrophobic membrane, reasonable mechanical strength, good gas permeability, high surface porosity, small in mean pore size and high absorption flux. The membranes surface roughness analyzed via atomic force microscope (AFM) showed that the mean surface roughness of the outer membrane was lower than inner membrane as the concentration of alumina and bentonite increased. PA5 and PB5 hollow fiber membranes possessed the highest contact angle values of 97.39° and 95.79°. PA5 and PB5 hollow fiber membrane showed the highest absorption flux in 1 M MEA of 3.89 × 10-2 mol/m2.s and 4.08 × 10-2 mol/m2.s at flow rate 200 ml/min, respectively. The CO2 absorption was repeated by using 2 M MEA as absorbent. The absorption flux of PA5 and PB5 hollow fiber membrane had increased up to 6.12 × 10-2 mol/m2.s and 6.35 × 10-2 mol/m2.s, respectively. The long-term absorption test was conducted with PA5 and PB5 hollow fiber membranes in 2 M MEA for 60 hours. From the long-term CO2 absorption flux, PA5 hollow fiber membrane showed much better performance than PB5 hollow fiber membrane. Therefore, PB5 membrane possessed a more sponge-like structure, high water contact angle, good mechanical strength, great gas permeability, high surface porosity with small mean pore size and demonstrated a higher absorption CO2 flux is preferred for CO2 membrane contactor application.